IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK BERBASIS APLIKASI SMART NETIZEN BIDANG KEPENDUDUKAN (Studi Pada Dinas Kependudukan dan Pencatatan Sipil Kota Malang) - Darmawan Darmawan; Taufiq Soeltanto (STIA MALANG, 2021)
Policy changes made by the government in the area of population services are aimed at achieving orderly populationmanagement. It plays an important role in government management and development. We support the implementationof SIAK in the population and citizen registration departments of Malang City and provide online services based onthe SmartNetizen application aimed at providing higher quality services to the community.This study aims to determine and analyze policy implementations for online service applications based on the SmartNetizen application of Malang City's Population and Citizen Registration Department. This study uses qualitativeresearch, collects data through interviews and documentation, analyzes the data using qualitative analysis, and usesqualitative analysis from Milles, Huberman, and Saldana's interactive analysis models. And investigate the purposeof the investigation. Find the problem and find the solution to the existing problem according to (2014).The results of the survey prove that applications for Smart Netizen application-based online services are supportedby the provision of an online web that is accessible 24 hours a day throughout the community. This service containsa variety of information that may be required in connection with the services available at the agency. You will find that it has a positive impact on service activities, such as the availability of necessary information related to thevarious purposes specified in the service, which can be accessed by the various applications used by netizens. Themechanism is believed to be unclear as the application for online services based on the Smart Netizen Applicationconducted by the City of Malang's Population and Citizen Registration Office is not supported by completeinformation such as population management systems and procedures. gain. Since the application for online servicesbased on the smart netizen application conducted by the Population and Citizen Registration Bureau of the city ofMalang has not yet spread to the community at the RT level, the system and procedure service for implementing theonline based on the smart netizen application is available. It has not yet been considered to have contributed to thecommunity in its efforts to improve the quality of service.Keywords: Implementation, Policy, Online Services, Smart Netizens